Where do I stand in the EU? Income comparisons and perceptions - Elisabeth Bublitz; Julian Jäger; Hequn Wang; Miriam Beblo; Henning Lohmann (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2022)
With a survey experiment conducted in Germany, Italy, Poland, and Sweden, we investigate how EU citizens rank themselves within the EU. In all four countries, (mis-)perceptions of EU income positions result primarily from respondents' (incomplete) information about their national position and their perceived country ranking within the EU. Low-income respondents tend to place themselves higher and richer respondents lower in both the national and EU income distribution. Respondents who are informed about their income position estimate their EU ranking more accurately in a follow-up survey. Our findings show that concepts of inequality at the EU level are empirically meaningful and that EU citizens have a reference frame beyond their own country.
Keywords: C91; D31; H24; 330; Perceptions; Inequality; European Union; Survey Experiment